Lipid droplet accumulation in microglia and their potential roles - Yunxia Li; Qi Zhao; Yan Wang; Wenyi Du; Riyun Yang; Jian Wu; Yi Li (Lipids in Health and Disease)
Abstract Microglia are the resident immune cells of the central nervous system (CNS), where lipid metabolism is critical for maintaining homeostasis. In response to various external stimuli, they demonstrate a range of phenotypic expressions and lipid metabolic reprogramming. Lipid droplets (LDs) are dynamic organelles that function beyond energy storage, actively participating in neuropathological progress. Recent investigations have identified a subset of microglia characterized by the accumulation of LDs, referred to as “lipid-droplet-accumulating microglia” (LDAM). This review aims to investigate the processes involved in LD formation and degradation, the factors that modulate them, focusing particularly on the function of LDAM and their implications for CNS disorders. By synthesizing current evidence, we clarify the biological significance of LDs in these cells and their therapeutic targeting potential, providing new directions for future research.